Márkus Dezső a nőkérdésről II.: Nőtartás a joggyakorlatban (1867–1918) - Császár, Kinga (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2021)
This paper shows the standpoints of the representatives of the legal practice about women’s legal status in Hungary between 1867 – 1918. The actuality of the examination was the fact that the drafts of the first Civil Code in Hungary (1900 –1928) were under editing at the same time. The articles about alimony and jointure are described in this paper. The study shows the attitude of the members of the legal profession towards the extension of women’s rights and the significant contradictions in case law.